Risk Factors for the Progression from Low to High Titres in 260 Children with Severe Haemophilia A and Newly Developed Inhibitors - Mancuso, Maria Elisa; Fischer, Kathelijn; Santagostino, Elena; Oldenburg, Johannes; Platokouki, Helen; Königs, Cristoph; Escuriola-Ettingshausen, Carmen; Rivard, George E.; Cid, Ana Rosa; Carcao, Manuel; Ljung, Rolf; Petrini, Pia; Altisent, Carmen; Kenet, Gili; Liesner, Raina; Kurnik, Karin; Auerswald, Günther; Chambost, Hérvè; Mäkipernaa, Anne; Molinari, Angelo Claudio; Williams, Mike; van den Berg, H. Marijke; on behalf of the European Pediatric Network for Haemophilia Management (PedNet) the REMAIN (REal life MAnagement of children with INhibitors) Study Group (Thrombosis and Haemostasis, 2017)
In children with severe haemophilia A, inhibitors to factor VIII (FVIII) usually develop during the first 50 treatment exposure days and are classified as low or high titre depending on the peak inhibitor titre being greater or less than 5 Bethesda units/mL (BU/mL). Classification of the inhibitor may change with time, as some low-titre inhibitors progress to high titre following re-exposure to FVIII concentrate. The aim of this study was to investigate potential risk factors for such a progression in children with severe haemophilia A and newly diagnosed inhibitors. This study was a follow-up study of the PedNet Registry and included 260 children with severe haemophilia A and inhibitors born between 1990 and 2009 and recruited consecutively from 31 haemophilia centres. Clinical and laboratory data were collected from the date of each child's first positive inhibitor test for at least 3 years. At the time of first positive inhibitor test, 49% (n = 127) had low-titre inhibitors, with 50% of them progressing to high titre and only 25% maintaining low titres. The FVIII gene (F8) mutation type was known in 247 patients (95%), and included 202 (82%) null mutations. The progression to high-titre inhibitors was associated with null F8 mutations (odds ratio [OR]: 2.6; 95% confidence interval [CI]: 1.0–6.5), family history of inhibitors (OR: 7.2; 95% CI: 1.8–28.4) and the use of high-dose immune tolerance induction, defined as ≥100 IU FVIII concentrate/kg/d (OR: 3.9; 95% CI: 1.5–10.0). These results suggest that high-dose immune tolerance induction should be avoided as the initial strategy in patients who develop low-titre FVIII inhibitors.
Keywords: haemophilia A; children; inhibitors; high titre; immune tolerance induction